KETIMPANGAN GENDER DALAM NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN MELALUI PERSPEKTIF FEMINISME - Eldaa Crystle Wenno; Henderika Serpara (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2023)
A novel is a literary work created by an author in the form of a long prose essay and contains a series of stories of a person's life that emphasizes his character and behaviour. The study aimed to describe the structural and existential elements of gender inequality in Eka Kurniawan's novel Cantik itu Luka. The study used two theories: structure theory and literary criticism of feminism that focuses on women as readers. Intrinsic elements of the novel will be examined using structural theories while feminist literary critique theories are used to examine gender inequality in the novel. The method used in this research is the descriptive qualitative method. The results of this study showed that (1) the structure in the novel Cantik itu Luka in the form of themes, plots, characters and strengthening, background, point of view, and mandate, (2) gender inequality that arises is in the form of gender inequality towards women through the perspective of feminism that leads to subordination that subordinates women, vulnerable to violence, negative stigma against women, and marginalization of women. This study suggest that a male writer must really understand women’s behaviors before writing about them.